Common Fixed Point Theorems via Measure of Noncompactness - Baboli, Alireza Valipour (Annals of Mathematics and Physics, 2024)
In this paper, by applying the measure of noncompactness a common fixed point for the maps T and S is obtained, where T and S are self-maps continuous, commuting continuously on a closed convex subset C of a Banach space E and also S is a linear map. Then as an application, the existence of a solution of an integral equation is shown.